2015
DOI: 10.1007/s12040-015-0559-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and outburst risk analysis of moraine-dammed lakes in the central Chinese Himalaya

Abstract: The recent evolution and outburst risk of two typical moraine-dammed lakes, Galong and Gangxi, central Chinese Himalaya, are analyzed using topographic maps from 1974 and Landsat satellite imagery acquired in 1988, 2000 and 2014. The datasets show the areas of Galong and Gangxi lakes increasing at rates of 0.45 and 0.34 km 2 /year during the period 1974-2014, an expansion of 501% and 107%, respectively, in the past 41 years, while the areas of the parent glaciers, Reqiang and Jipucong decreased by 44.22% and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…A comparison of topographic maps from 1974 and Landsat imagery for 2014 reveals that Galongco and Gangxico lakes expanded by ~500% (0.45 km 2 a −1 ) and ~107% (0.34 km 2 a −1 ) respectively over this period. This expansion corresponds to an area shrinkage of their parent glaciers of Jipucong and Reqiang of ~40% (~0.07 km 2 a −1 ) (Wang and Jiao, 2015). Seven lakes, including Galonco, Gangxico, Youmojianco and Cirenmaco in the basin have previously been identified as PDGLs based on high rates of expansion and a semiquantitative method considering other factors relevant for lake stability (Chen and others, 2007a; Wang and others, 2014).…”
Section: Previous Studies In the Poiqu River Basinmentioning
confidence: 99%
See 3 more Smart Citations
“…A comparison of topographic maps from 1974 and Landsat imagery for 2014 reveals that Galongco and Gangxico lakes expanded by ~500% (0.45 km 2 a −1 ) and ~107% (0.34 km 2 a −1 ) respectively over this period. This expansion corresponds to an area shrinkage of their parent glaciers of Jipucong and Reqiang of ~40% (~0.07 km 2 a −1 ) (Wang and Jiao, 2015). Seven lakes, including Galonco, Gangxico, Youmojianco and Cirenmaco in the basin have previously been identified as PDGLs based on high rates of expansion and a semiquantitative method considering other factors relevant for lake stability (Chen and others, 2007a; Wang and others, 2014).…”
Section: Previous Studies In the Poiqu River Basinmentioning
confidence: 99%
“…1). Previous studies identified the high level of risk in this basin, as the potential for GLOF hazards is high and any outburst could severely affect livelihoods and infrastructure (Khanal and others, 2015; Wang and others, 2015). This basin also has the highest ratio of glacier area to lake area in the Hindu-Kush-Karakoram-Himalaya (HKH) regions (Wang and others, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The vast majority of the case studies on cryosphere disservices are on glacial lake outburst floods (GLOFs), indicating their importance as a cause of great socioeconomic losses in the HKH (Iturrizaga 2005;Shijin and Shitai 2015) and in some instances far downstream (Allen et al 2016). Bhutan and Nepal have recently been recognized as the two countries facing the greatest economic consequences from GLOFs worldwide (Carrivick and Tweed 2016), including threats to the unique cultural heritage (Kropáček et al 2015;Sherry et al 2018).…”
Section: Disservices: Cryosphere-related Disastersmentioning
confidence: 99%